1987
DOI: 10.1038/jcbfm.1987.50
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Temporal Lobe Response in Alzheimer's Disease during Cognitive Processing as Measured by 11C-2-Deoxy-D-Glucose and PET

Abstract: Elderly controls and probable Alzheimer's disease patients underwent serial positron emission tomography (PET) studies during a baseline condition and while performing a verbal memory task. for the temporal lobes, all 7 Alzheimer patients demonstrated a relative shift in glucose metabolic rates to the right hemisphere during the memory condition relative to baseline, and 5 of 7 controls showed a shift to the left hemisphere. Baseline absolute regional metabolic rates replicate previous findings and were somewh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
2

Year Published

1989
1989
2006
2006

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(20 citation statements)
references
References 11 publications
3
15
2
Order By: Relevance
“…While temporal areas (21,22) show major decreases, parietal areas 5 and 7 do not. Our results are most similar to those of Miller et al [30], who used a memory uptake task and statistically confirmed only temporal metabolic rate deficits. Temporal/auditory areas 41 and 42 showed higher rates in AD patients than in controls.…”
Section: Discussionsupporting
confidence: 81%
“…While temporal areas (21,22) show major decreases, parietal areas 5 and 7 do not. Our results are most similar to those of Miller et al [30], who used a memory uptake task and statistically confirmed only temporal metabolic rate deficits. Temporal/auditory areas 41 and 42 showed higher rates in AD patients than in controls.…”
Section: Discussionsupporting
confidence: 81%
“…This might suggest that the brain first tries to compensate for a deficient cognitive function by involving more cortical areas, including even those not strictly deputed to the task, a mechanism which has previously been described for motor and language recovery [20]. This observation is in accordance with studies by Gur et al [21], Miller et al [22]and Duara et al [23], who described contralateral brain activity in AD patients during the performance of a cognitive task compared with controls. Recently, Becker et al [24]and Woodard et al [25]demonstrated in AD patients an apparent increase in the size of the areas that were normally activated during a memory task by controls.The lack of activation in subcortical regions observed in vascular patients, when compared with controls, is probably due to the fact that most of our patients had lacunar infarctions which selectively involved these areas.…”
Section: Discussionsupporting
confidence: 82%
“…Using topographic mapping of computerized EEGs, Duffy et al (1984) found right temporal slow activity in younger patients with Alzheimer's disease and frontal slow activity in older patients. The new capacity for regional analysis of functional activity offered by positron emission tomography has also been applied in Alzheimer's disease (Friedland et al 1985;Duara et al 1986;Miller et al 1987). They report decreased temporal/parietal metabolic rates without occipital decreases -a pattern consistent with the histopathology and the topographic findings of Duffy et al (1984).…”
mentioning
confidence: 78%